2003
DOI: 10.1046/j.1442-9071.2003.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual loss in sarcoid‐related uveitis

Abstract: Multifocal choroiditis is a less common manifestation of uveitis associated with sarcoidosis but appears to be associated with a worse visual prognosis despite immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
3
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 25 publications
4
53
3
1
Order By: Relevance
“…To increase its relevance and favour comparisons with previous studies,5–7 11 histological proof and exclusion of other granulomatous diseases were required for inclusion. This step matches the first level of diagnosis outlined in the International Workshop on Sarcoidosis 12.…”
Section: Discussionmentioning
confidence: 99%
“…To increase its relevance and favour comparisons with previous studies,5–7 11 histological proof and exclusion of other granulomatous diseases were required for inclusion. This step matches the first level of diagnosis outlined in the International Workshop on Sarcoidosis 12.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Experimental autoimmune uveitis (EAU) is an animal model of human autoimmune uveitis and has been widely used for dissecting mechanisms and developing treatment strategies. 5 EAU is induced by immunization with retinal antigens such as interphotoreceptor retinoid-binding protein (IRBP), 6,7 and activated and sensitized Th1 and Th17 cells are considered to play a major role in initiation and maintenance of the intraocular inflammation.…”
mentioning
confidence: 99%
“…2b). There are a few reports on associations of APMPPE with either probable sarcoidosis [1,2] or CNS abnormalities [3]. Histopathological studies have shown the latter to be caused by granulomatous arteritis of medium-sized arteries [4].…”
mentioning
confidence: 99%